Method for preparing ultrapure titanium tetrachloride through membrane filtration and adsorption

By controlling the thickness and flow rate of the microfiltration membrane, the membrane filtration and adsorption of polytetrafluoroethylene microfiltration membrane is used to solve the problem of removing trace metal impurities in titanium-based electronic-grade chemicals, and the efficient and simple ultra-pure tetrachloride is achieved. Titanium preparation.

CN119461469APending Publication Date: 2025-02-18CHINA SILICON CORP LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411881958.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove trace metal impurities in titanium-based electronic grade chemicals, especially when reaching the G4 level purity (10-10), there are problems such as removal limit, unstable quality, and high energy consumption for purification and separation.

Method used

By controlling the thickness of the microfiltration membrane and the rate of the titanium tetrachloride flow membrane, using the membrane filtration adsorption characteristics, the polytetrafluoroethylene microfiltration membrane is used as the adsorption layer, and the pressure is driven to pass through ultrapure under a nitrogen atmosphere under pressure. Microfiltration membrane achieves efficient adsorption and removal of trace metal impurities in titanium tetrachloride.

Benefits of technology

It realizes efficient removal of trace metal impurities in titanium tetrachloride. The process has the advantages of simple operation, gentle conditions, high removal efficiency and environmentally friendly, and can prepare ultrapure electronic grade chemical titanium tetrachloride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461469A_ABST
    Figure CN119461469A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of a titanium-based material titanium tetrachloride for an integrated circuit, and relates to a method for removing trace impurities of electronic-grade chemicals, in particular to a method for preparing ultrapure titanium tetrachloride through membrane filtration and adsorption, which comprises the following steps: S1, performing ultrasonic treatment on a microfiltration membrane in ultrapure water to obtain an ultrapure microfiltration membrane; s2, flatly placing the ultra-pure micro-filtration membrane in a drying oven for drying, and removing internal moisture; and S3, enabling the titanium tetrachloride stock solution to penetrate through the dried ultra-pure micro-filtration membrane under pressure driving, so as to prepare the ultra-pure titanium tetrachloride. The method can efficiently adsorb trace metal impurities in titanium tetrachloride, and the whole filtration and adsorption process has the advantages of being simple and convenient to operate, mild in condition, high in removal efficiency, environmentally friendly and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of titanium tetrachloride, a titanium-based material for integrated circuits, and relates to a method for removing trace impurities of electronic-grade chemicals, in particular to a method for preparing ultrapure titanium tetrachloride by membrane filtration and adsorption. Background Art

[0002] Ultrapure electronic-grade chemicals are basic materials used in the manufacturing process of microelectronics and integrated circuits. They are widely used in processes such as silicon wafers, thin film deposition, and photolithography. They have the characteristics of high technical barriers and rapid product updates. They are one of the key factors that determine product performance, integration, and yield. With the gradual reduction of the feature size of integrated circuits and the transfer of processing from plane to three-dimensional, especially 28nm and more advanced process technologies, higher requirements are placed on ultrapure electronic-grade chemicals, including product component purity greater than 99.9%, and metal impurity content requirements of 10 -10 (Grade G4).

[0003] From the perspective of separation and purification technology, ultrapure electronic-grade chemicals are volatile and can be purified by distillation in theory. At present, distillation can easily reduce the impurity ion content in electronic chemicals from 10 -6 Raised to 10 -9 (G3 grade). However, the distillation process only relies on the difference in boiling points between the impurity component and the target component, and it is difficult to deeply remove components with similar boiling points. Due to the diverse occurrence states of impurities and their interactions, impurities with similar boiling points often exist, and it is possible to form azeotropes, etc., making it difficult to directly obtain G4 grade electronic chemicals by distillation. In addition, titanium-based electronic-grade chemicals often have a high boiling point (>120℃) and latent heat of vaporization (>700kJ / kg), and the distillation method has high energy consumption. In addition to the distillation method, the deep impurity removal technologies for electronic-grade chemicals that are currently being studied more include adsorption and crystallization. Among them, the adsorption method introduces a competitive adsorption mechanism, relying on the difference in the strength of the interaction between the adsorption site and the impurity component and the target component, to promote the preferential adsorption of impurity ions, and there is a technical possibility of further removing impurity components. However, the traditional fixed bed adsorption has a large bed gap, and the impurity component still has a high probability of "escaping" through the gap, making it difficult to remove the impurity component to a concentration level of 10-10 within a limited bed height. Although the melt crystallization method can theoretically obtain high-purity crystals, it is difficult to avoid the adsorption of impurities on the surface of the product. The current purification level is similar to that of distillation, and it is also difficult to obtain G4-grade products. In general, effective separation cannot be achieved only through conventional distillation and adsorption crystallization technology. There are problems such as removal limits, unstable quality, high energy consumption for purification and separation, and high system equipment investment.

[0004] The emerging membrane separation technology has shown great potential in extraordinary separation due to its advantages of being green, energy-saving, efficient, and highly selective. Conventional membrane filtration, reverse osmosis and other technologies, although they can use the difference in diffusion rate between the target component and the impurity component to achieve separation, the residence time of the component diffusion across the membrane is usually short, and it is difficult to control the diffusion of impurities across the membrane at a sufficiently low level. If the membrane thickness is greatly increased to extend the residence time, the process will be reduced to an adsorption technology. Therefore, for a long time, membrane technology has been ignored and even considered not to be an effective option for the purification of electronic-grade chemicals. However, membrane technology has another advantage, that is, it is easy to couple with other separation technologies to form an integrated unit operation, such as distillation, membrane extraction, membrane crystallization, membrane filtration adsorption, membrane reactors, etc., thereby playing a role in complementary advantages. However, the method of removing trace impurities in electronic chemicals by membrane filtration adsorption has not yet been reported.

[0005] Therefore, those skilled in the art are in urgent need of developing a method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption that is simple to operate, has mild conditions, high removal efficiency and is environmentally friendly, so as to more efficiently adsorb trace metal impurities in titanium tetrachloride. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing titanium tetrachloride as an electronic chemical, by controlling the thickness of the microfiltration membrane and the rate at which titanium tetrachloride flows through the membrane, making full use of the characteristics of membrane filtration and adsorption, and solving various shortcomings of titanium tetrachloride products based on titanium-based compounds in existing production technologies.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption comprises the following steps:

[0009] S1, subjecting the microfiltration membrane to ultrasonic treatment in ultrapure water to obtain an ultrapure microfiltration membrane;

[0010] S2. Place the ultra-pure microfiltration membrane flat in an oven for drying to remove internal moisture;

[0011] S3. The titanium tetrachloride stock solution is driven by pressure to pass through the dried ultra-pure microfiltration membrane to obtain ultra-pure titanium tetrachloride.

[0012] Preferably, in step S1, the microfiltration membrane is made of polytetrafluoroethylene or nylon 66. More preferably, the microfiltration membrane is made of polytetrafluoroethylene microfiltration membrane which is resistant to strong acid, corrosion and high chemical stability.

[0013] Preferably, in step S1, the time of ultrasonic treatment of the microfiltration membrane is 0.5 h, the ultrapure water is kept at a constant temperature of 25° C., the number of ultrasonic treatments is 2 times, and the pure water is replaced 2 times.

[0014] Preferably, in step S1, the total metal impurity content of ultrapure water is less than 1000 ppb.

[0015] Preferably, in step S1, the ratio of ultrapure water to microfiltration membrane is 2.5:1, and the comparison unit is L:m 2 .

[0016] Preferably, in step S2, the drying temperature of the ultrapure microfiltration membrane is 60° C., and the drying time is 24 hours.

[0017] Preferably, in step S2, the drying atmosphere of the ultrapure microfiltration membrane is a nitrogen atmosphere.

[0018] Preferably, in step S3, the dried ultra-pure microfiltration membrane is placed in a filtration adsorption device, and the titanium tetrachloride stock solution is pressure-driven to pass through the ultra-pure microfiltration membrane under a nitrogen atmosphere, and the material of the filtration adsorption device is polytetrafluoroethylene.

[0019] Preferably, the filtering and adsorption device comprises a cylindrical shell and a cover body detachably and sealably connected to the top of the shell, the top of the cover body is provided with a nitrogen inlet, and the nitrogen inlet is provided with a nitrogen switch valve, the top side of the shell is provided with a feed inlet, the bottom side is provided with a discharge port, and the middle part of the shell is provided with an annular support plate, and the ultra-pure microfiltration membrane after drying in step S3 is fixed on the support plate. More preferably, the ultra-pure microfiltration membrane is clamped in a membrane frame, and the membrane frame is fixedly connected to the support plate by bolts.

[0020] Preferably, in step S3, the ratio of titanium tetrachloride stock solution to ultra-pure microfiltration membrane is 5:2, and the comparison unit is L:m 2 .

[0021] Preferably, it is characterized in that: in step S1, the thickness of the microfiltration membrane is 0.5-1 mm.

[0022] Preferably, in step S1, the thickness of the microfiltration membrane is 0.767 mm.

[0023] Preferably, in step S3, the flux of the titanium tetrachloride stock solution is 2 to 10 L m -2 h -1 bar -1 .

[0024] Preferably, in step S3, the flux of the titanium tetrachloride stock solution is 5 L m -2 h -1 bar -1 .

[0025] Preferably, in step S3, the dried ultra-pure microfiltration membrane is used as an adsorption layer to adsorb and remove trace metal impurity elements in titanium tetrachloride.

[0026] Preferably, in step S3, the dried ultra-pure microfiltration membrane is placed in a membrane pool, and the trace impurity metal ions in titanium tetrachloride are adsorbed by the microfiltration membrane in a pressure-driven manner under a nitrogen atmosphere.

[0027] Preferably, in step S3, the dried ultrapure microfiltration membrane is directly placed in the titanium tetrachloride stock solution, and the trace impurity metal ions in the titanium tetrachloride are adsorbed by stirring.

[0028] In the present invention, in the titanium tetrachloride stock solution, the total content of metal impurities is less than 50 ppb, the key element arsenic is less than 7 ppb, and the tin is less than 4 ppb.

[0029] The present invention also includes other devices or steps that enable it to be used normally, which are all conventional technical means in the field; in addition, the devices or steps not limited in the present invention all adopt conventional means in the field and will not be described in detail here.

[0030] The working principle of the present invention is:

[0031] The present invention places the dried ultra-pure microfiltration membrane in a filtration and adsorption device, takes a certain amount of titanium tetrachloride stock solution, drives the titanium tetrachloride flow through the ultra-pure microfiltration membrane by nitrogen pressure, and uses the ultra-pure microfiltration membrane to adsorb trace impurity ions in the titanium tetrachloride, thereby preparing ultra-pure electronic chemical titanium tetrachloride. The microfiltration membrane of the present invention is a separation membrane made of organic high molecular polymer as a material, and the separation membrane can also be prepared using any film-forming high molecular material. High molecular polymers are widely used in the preparation of various membrane separation processes, because high molecular membranes usually have a large surface area and rich active sites; they have excellent ability to adsorb target substances. The large pore characteristics of the microfiltration membrane can maintain a good production capacity in the filtration and adsorption process even under very low pressure differences, and reduce energy consumption, which is conducive to the mass production of high-purity titanium tetrachloride.

[0032] Taking polytetrafluoroethylene microfiltration membrane as an example, on the one hand, polytetrafluoroethylene microfiltration membrane has strongly bonded fluorine atoms and exhibits semi-crystalline properties. The close combination of the carbon main chain and the fluorine atoms will not cause PTFE to react with any other compound, thereby reducing the oxidative corrosion of titanium tetrachloride to the membrane material. In addition, titanium tetrachloride is also a strong acid compound that reacts with water to produce hydrochloric acid and titanium dioxide. At the same time, it has oxidizing properties and can react with many organic and inorganic substances to cause combustion. Therefore, polytetrafluoroethylene materials can coexist well with titanium tetrachloride. On the other hand, the fluorine group has a strong affinity with metal ions, and the lone pair of electrons in the fluorine group can coordinate with the 4f orbit of the metal ion, providing a path for the adsorption and removal of metal impurities, thereby realizing the adsorption and removal of metal ions. The pore size of the polytetrafluoroethylene microfiltration membrane is 0.22 microns, which can ensure the smooth passage of titanium tetrachloride stock solution even at a very low pressure difference. At the same time, polytetrafluoroethylene materials have good non-adhesive properties and are easy to remove dust accumulated on the surface of the material, so they can be washed with water to restore performance, achieve repeated use, and greatly extend the service life.

[0033] In general, the present invention uses a microfiltration membrane as an adsorption layer. The microfiltration membrane with corrosion resistance and oxidation resistance ensures the integrity of its own structure while removing trace metal impurities, which makes it possible to reuse the membrane material. In addition, membrane filtration adsorption technology has the advantages of both adsorption and filtration, overcoming the shortcomings of "adsorption escape" in the adsorption process and too short residence time in the membrane filtration process. The microfiltration membrane used in this application has a narrow mass transfer channel, can efficiently "capture" impurity ions, and can quickly pass through the target component. This also provides some new ideas for the subsequent development of adsorption functional membranes.

[0034] The beneficial effects of the present invention are:

[0035] The invention can efficiently adsorb trace metal impurities in titanium tetrachloride, and the entire filtration and adsorption process has the advantages of simple operation, mild conditions, high removal efficiency, environmental friendliness, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The SEM surface images of the microfiltration membranes obtained in Examples 2 to 3 of the present invention and Comparative Examples 1 to 2 are shown;

[0037] Figure 2 This is a low-magnification SEM surface image of the microfiltration membrane before and after adsorption in Example 1 of the present invention;

[0038] Figure 3 The infrared spectra of each microfiltration membrane before and after ethanol washing in Examples 2 to 3 of the present invention and Comparative Examples 1 to 2 are shown;

[0039] Figure 4It is a static performance diagram of each microfiltration membrane before and after adsorbing trace impurities in titanium tetrachloride in Example 3 of the present invention and Comparative Examples 1-2;

[0040] Figure 5 It is a static performance diagram of each microfiltration membrane in Examples 2 to 3 of the present invention for adsorbing trace impurities in titanium tetrachloride;

[0041] Figure 6 This is a dynamic performance diagram of the microfiltration membrane adsorbing trace impurities in titanium tetrachloride in Example 1 of the present invention;

[0042] Figure 7 This is a data table of the adsorption of trace impurities in titanium tetrachloride by the microfiltration membrane in Example 1 of the present invention;

[0043] Figure 8 It is a schematic diagram of the structure of the adsorption and filtration device in Example 4 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described below with the accompanying drawings and specific examples. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0045] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0046] There is no particular limitation on the purity of all raw materials in the present invention, but electronic purity is preferred in the present invention.

[0047] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.

[0048] Example 1

[0049] A method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption comprises the following steps:

[0050] S1, the microfiltration membrane is ultrasonically treated in ultrapure water to obtain an ultrapure microfiltration membrane; the microfiltration membrane is ultrasonically treated for 0.5h, and the ultrapure water is kept at a constant temperature of 25°C, the number of ultrasonic treatments is 2 times, and the pure water is replaced 2 times; the total metal impurity content of the ultrapure water is less than 1000ppb; the ratio of ultrapure water to microfiltration membrane is 2.5:1, and the comparison unit is L:m 2 , the thickness of the microfiltration membrane is 0.767 mm;

[0051] S2, placing the ultra-pure microfiltration membrane in a drying oven and placing it flat to prevent mutual adhesion and remove internal moisture; the drying temperature of the ultra-pure microfiltration membrane is 60°C, the drying time is 24h, and the drying atmosphere is nitrogen atmosphere.

[0052] S3, placing the titanium tetrachloride stock solution and the dried ultra-pure microfiltration membrane into a filtration adsorption device and driving the device under pressure to obtain ultra-pure titanium tetrachloride; the filtration adsorption device is made of polytetrafluoroethylene, and the pressure atmosphere is nitrogen; the ratio of the titanium tetrachloride stock solution to the ultra-pure microfiltration membrane is 5:2, and the comparison unit is L:m 2 ; The flux of titanium tetrachloride stock solution is 5L m -2 h -1 bar -1 .

[0053] In this embodiment, the microfiltration membrane is a polytetrafluoroethylene microfiltration membrane, denoted as PTFE.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the trace metal impurities in titanium tetrachloride are statically adsorbed by using a dried ultra-pure microfiltration membrane in a stirring manner, and the microfiltration membrane is PTFE.

[0056] Example 3

[0057] The only difference between this embodiment and embodiment 2 is that the microfiltration membrane used is a nylon 66 microfiltration membrane, denoted as Nylon 66.

[0058] Example 4

[0059] like Figure 8 As shown, on the basis of Example 1, the filtering and adsorption device of this embodiment includes a cylindrical shell 1 and a cover body 2 detachably and sealably connected to the top of the shell, the top of the cover body is provided with a nitrogen inlet 3, and the nitrogen inlet is provided with a nitrogen switch valve, the top side of the shell is provided with a feed port 5, the bottom side is provided with a discharge port 6, the feed port is provided with a feed valve, the discharge port is provided with a discharge valve, and the middle part of the shell is provided with an annular support plate 7, and the ultra-pure microfiltration membrane 4 after drying in step S3 is fixed on the support plate. Specifically, the ultra-pure microfiltration membrane is clamped in a membrane frame (not shown in the figure), and the membrane frame is fixedly connected to the support plate by bolts (not shown in the figure).

[0060] Comparative Example 1

[0061] The only difference between this comparative example and Example 2 is that the microfiltration membrane used is a polyvinylidene fluoride microfiltration membrane, denoted as PVDF.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 2 is that the microfiltration membrane used is a polyethersulfone microfiltration membrane, denoted as PES.

[0064] Comparative analysis:

[0065] The microfiltration membranes in Examples 2-3 and Comparative Examples 1-2 are compared as follows:

[0066] like Figure 1 Shown are SEM surface images of microfiltration membranes obtained in Example 2, Example 3, Comparative Example 1, and Comparative Example 2 of the present invention;

[0067] The porous structure of the microfiltration membrane can be clearly seen on the SEM surface. Compared with Nylon 66, PVDF, and PES, the PTFE surface is relatively rough and has a unique front and back structure. This feature provides a reasonable change in the flux of the titanium tetrachloride stock solution when the polytetrafluoroethylene microfiltration membrane is filtering and adsorbing, and prolongs the circulation time of the titanium tetrachloride stock solution between the microfiltration membranes.

[0068] like Figure 2 Shown is a low-magnification SEM surface image of the microfiltration membrane before and after adsorption in Example 2 of the present invention.

[0069] The SEM on the back of the polytetrafluoroethylene can clearly show that when the titanium tetrachloride raw material flows through the microfiltration membrane and contacts the air, a large number of white particles will accumulate on the PTFE membrane. This phenomenon is closely related to the physical properties of titanium tetrachloride. When titanium tetrachloride contacts the air, it will quickly react with the oxygen and water in the air to generate titanium dioxide and hydrogen chloride. The generated substances will seriously contaminate the membrane material. The results on the front and back of the PTFE membrane are similar, and both have serious pore blockage.

[0070] like Figure 3 Shown are infrared spectra of Example 2, Example 3, Comparative Example 1, and Comparative Example 2 before and after adsorption and ethanol washing.

[0071] Comparing the infrared spectra of the membranes before and after the adsorption of titanium tetrachloride stock solution, it can be clearly seen that some positions in the PVDF membrane structure are shifted, which indicates that the strong oxidizing and acidic properties of titanium tetrachloride seriously react with the PVDF membrane material. However, no obvious changes were found in the infrared spectra of PTFE, Nylon 66 and PES, indicating the compatibility and stability of these three membranes with titanium tetrachloride.

[0072] like Figure 4 Shown are static performance diagrams of the microfiltration membranes in Example 3, Comparative Example 1, and Comparative Example 2 of the present invention for adsorbing trace impurities in titanium tetrachloride.

[0073] The static adsorption experiments of Example 3, Comparative Example 1 and Comparative Example 2 were carried out using titanium tetrachloride solution. The solution used in the test was a titanium tetrachloride stock solution containing a relatively high impurity concentration, wherein the total metal impurity content of the titanium tetrachloride stock solution used for Nylon 66 was less than 11000 ppb, and the total metal impurity content of the titanium tetrachloride stock solution used for PVDF and PES was less than 700 ppb. The test conditions were: 20 ml of titanium tetrachloride stock solution was mixed with 80 cm 2 Nylon 66, PVDF and PES were placed in a 50 ml beaker and stirred at room temperature for 10 min at a stirring speed of 50 rpm. The data obtained are as follows Figure 4 As shown in the figure, compared with PVDF and PES, Nylon66 has a certain removal effect on trace impurity elements in titanium tetrachloride, with a removal rate of 56.25% for As and 28.92% for Sn. However, PVDF and PES have no obvious removal ability for trace impurity elements in titanium tetrachloride.

[0074] like Figure 5 Shown are static performance diagrams of adsorbing trace impurities in titanium tetrachloride by Examples 2 and 3 of the present invention.

[0075] The static adsorption experiments of Examples 2 and 3 were carried out using titanium tetrachloride solution. The solution used in the test was a titanium tetrachloride stock solution with a relatively low impurity concentration, with a total metal impurity content of less than 50 ppb. The test conditions were: 20 ml of titanium tetrachloride stock solution was mixed with 80 cm 2 Nylon 66 and PTFE were placed in a 50ml beaker and stirred at room temperature for 10 minutes at a stirring speed of 50 rpm. The data obtained are as follows Figure 5 As shown. The key elements V, As, and Sn all showed significant changes. After adsorption by Nylon 66, the V content increased, while the As and Sn contents decreased significantly, but still not less than 0.1ppb, which did not meet the G4 product requirements. In comparison, after PTFE membrane treated titanium tetrachloride stock solution, the V and As content was less than 0.1ppb, meeting the G4 product requirements. However, the Sn element increased slightly.

[0076] like Figure 6 As shown, it is a dynamic performance diagram of the microfiltration membrane in Example 1 of the present invention for adsorbing trace impurities in titanium tetrachloride.

[0077] like Figure 7 The figures show the statistical results of the static and dynamic performance of the microfiltration membrane in Example 1 of the present invention in adsorbing trace impurities in titanium tetrachloride.

[0078] The adsorption experiment of Example 1 was carried out using titanium tetrachloride solution. The solution used in the test was a titanium tetrachloride stock solution with a relatively low impurity concentration, with a total metal impurity content of less than 50 ppb. The test conditions were: 20 ml of titanium tetrachloride stock solution was mixed with 80 cm 2 , thickness is 0.767 mm, titanium tetrachloride flux is 5 L m -2 h -1 bar -1 Dynamic adsorption filtration was carried out under the pressure of nitrogen atmosphere. The material of the adsorption filtration device used was polytetrafluoroethylene. The data obtained are as follows Figure 6 , Figure 7 As shown. Among them, the key elements V, As, and Sn all showed significant changes. After static and dynamic adsorption by PTFE membrane, the three elements were significantly reduced. Figure 5 The static adsorption data of PTFE shown above shows that the Sn content is reduced by 50% after dynamic adsorption. More than ten impurity elements have been reduced to 0.1ppb.

[0079] The working principle of the present invention is:

[0080] The present invention places the dried ultra-pure microfiltration membrane in a filtration and adsorption device, takes a certain amount of titanium tetrachloride stock solution, drives the titanium tetrachloride flow through the ultra-pure microfiltration membrane by nitrogen pressure, and uses the ultra-pure microfiltration membrane to adsorb trace impurity ions in the titanium tetrachloride, thereby preparing ultra-pure electronic chemical titanium tetrachloride. The microfiltration membrane of the present invention is a separation membrane made of organic high molecular polymer as a material, and the separation membrane can also be prepared using any film-forming high molecular material. High molecular polymers are widely used in the preparation of various membrane separation processes, because high molecular membranes usually have a large surface area and rich active sites; they have excellent ability to adsorb target substances. The large pore characteristics of the microfiltration membrane can maintain a good production capacity in the filtration and adsorption process even under very low pressure differences, and reduce energy consumption, which is conducive to the mass production of high-purity titanium tetrachloride.

[0081] The present invention adopts polytetrafluoroethylene microfiltration membrane to have a relatively better effect. On the one hand, the polytetrafluoroethylene microfiltration membrane has a strongly bonded fluorine atom and exhibits a semi-crystalline property. The close combination of the carbon main chain and the fluorine atom will not cause PTFE to react with any other compound, thereby being able to weaken the oxidative corrosion of titanium tetrachloride to the membrane material. In addition, titanium tetrachloride is also a strongly acidic compound, which reacts with water to produce hydrochloric acid and titanium dioxide, and has oxidizability to react with many organic and inorganic substances to cause combustion. Therefore, polytetrafluoroethylene materials can coexist well with titanium tetrachloride. On the other hand, the fluorine group has a strong affinity with metal ions, and the lone pair of electrons in the fluorine group can coordinate with the 4f orbit of the metal ion, providing a path for the adsorption and removal of metal impurities to achieve the adsorption and removal of metal ions. The pore size of the polytetrafluoroethylene microfiltration membrane is 0.22 microns, which can ensure the smooth passage of titanium tetrachloride stock solution even at a very low pressure difference. At the same time, the polytetrafluoroethylene material has good non-adhesive properties, and it is easy to remove dust accumulated on the surface of the material, so it can be washed with water to restore its performance and achieve repeated use, greatly extending its service life.

[0082] In general, the present invention uses a microfiltration membrane as an adsorption layer. The microfiltration membrane with corrosion resistance and oxidation resistance ensures the integrity of its own structure while removing trace metal impurities, which makes it possible to reuse the membrane material. In addition, membrane filtration adsorption technology has the advantages of both adsorption and filtration, overcoming the shortcomings of "adsorption escape" in the adsorption process and too short residence time in the membrane filtration process. The microfiltration membrane used in this application has a narrow mass transfer channel, can efficiently "capture" impurity ions, and can quickly pass through the target component. This also provides some new ideas for the subsequent development of adsorption functional membranes.

[0083] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption, characterized in that: The following steps are involved: S1, subjecting the microfiltration membrane to ultrasonic treatment in ultrapure water to obtain an ultrapure microfiltration membrane; S2. Place the ultra-pure microfiltration membrane flat in an oven for drying to remove internal moisture; S3. The titanium tetrachloride stock solution is driven by pressure to pass through the dried ultra-pure microfiltration membrane to obtain ultra-pure titanium tetrachloride.

2. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 1, characterized in that: In step S1, the material of the microfiltration membrane is polytetrafluoroethylene or nylon 66, and the thickness of the microfiltration membrane is 0.5-1 mm.

3. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 1, characterized in that: In step S1, the microfiltration membrane is ultrasonically treated for 0.5 h, the ultrapure water is kept at a constant temperature of 25°C, the ultrasonic treatment is performed twice, and the pure water is replaced twice.

4. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 1, characterized in that: In step S1, the total metal impurity content of ultrapure water is less than 1000 ppb, and the ratio of ultrapure water to microfiltration membrane is 2.5:1, and the comparison unit is L:m 2 .

5. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 1, characterized in that: In step S2, the drying temperature of the ultra-pure microfiltration membrane is 60° C., the drying time is 24 h, and the drying atmosphere of the ultra-pure microfiltration membrane is a nitrogen atmosphere.

6. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 1, characterized in that: In step S3, the dried ultra-pure microfiltration membrane is placed in a filtration adsorption device, and the titanium tetrachloride stock solution is pressure-driven to pass through the ultra-pure microfiltration membrane under a nitrogen atmosphere. The material of the filtration adsorption device is polytetrafluoroethylene, and the ratio of the titanium tetrachloride stock solution to the ultra-pure microfiltration membrane is 5:

2. The comparison unit is L:m 2 .

7. A method for preparing ultrapure titanium tetrachloride by membrane filtration and adsorption according to any one of claims 1 to 6, characterized in that: In step S3, the flux of titanium tetrachloride stock solution is 2 to 10 L m -2 h -1 bar -1 .

8. A method for preparing ultrapure titanium tetrachloride by membrane filtration and adsorption according to any one of claims 1 to 6, characterized in that: In step S3, the dried ultra-pure microfiltration membrane is used as an adsorption layer to adsorb and remove trace metal impurity elements in titanium tetrachloride.

9. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 8, characterized in that: In step S3, the dried ultra-pure microfiltration membrane is placed in a membrane pool, and the trace impurity metal ions in titanium tetrachloride are adsorbed by the microfiltration membrane in a pressure-driven manner under a nitrogen atmosphere.

10. The method for preparing ultrapure titanium tetrachloride by membrane filtration adsorption according to claim 8, characterized in that: In step S3, the dried ultra-pure microfiltration membrane is directly placed in the titanium tetrachloride stock solution, and the trace impurity metal ions in the titanium tetrachloride are adsorbed by stirring.

Citation Information

Cited By

  • Industrial grade titanium tetrachloride purification and refining process

    CN121536954A